Brand Sustainability Development Goals Through the #SekarangUntukMasaDepan Message at PT Bank CIMB Niaga Tbk Regarding SDGs Program from the Perspective of Internal Audience - Joel Nathaniel Sobo; Nathalia Perdhani Soemantri (International Journal of Environmental Communication (ENVICOMM), 2024)
SDGs stands for Sustainable Development Goals, a set of objectives adopted by the UN in 2015 to achieve global sustainability by 2030. In fact, Indonesia still falls significantly short of UNDP standards in achieving the 17 SDGs. Additionally, awareness of SDGs among Indonesian society remains low, and the government is perceived as lacking in educating about SDGs. Indonesia implements SDGs programs through the Financial Services Authority (OJK), under government oversight, mandating participation in SDGs activities. OJK views Indonesia's Sustainable Finance Initiative (IKBI) as a genuine commitment from the banking industry. The research aims to understand PT Bank CIMB Niaga Tbk's Sustainable Development Goals branding efforts in creating internal branding through the #SekarangUntukMasaDepan message. This study employs a post-positivist paradigm with a descriptive qualitative approach, focusing on CIMB Niaga's internal branding of SDGs through the #SekarangUntukMasaDepan message via interviews and observations. Research findings indicate that CIMB Niaga has engaged in internal branding through the #SekarangUntukMasaDepan message, utilizing SDGs programs such as Start Small, Here for Everywhere, and Experimental events related to SDGs branding.